THE ROLE OF E-GOVERNMENT IN ENHANCING E-DEMOCRACY IN SELANGOR LOCAL GOVERNMENTS: AN EVALUATIVE STUDY - Nazreena binti Mohammed Yasin (Journal of Islamic, Social, Economics and Development, 2022)
Electronic government (e-Government) is a research field that studies the use ofinformation and communication technology (ICT) in the public sector. E-Government aims topromote people's participation by using the services provided by the government and utilisingmodern technology to increase democratic engagement. This study uses Marianne Kneuer'sframework to examine the impact of e-government on democracy in Selangor. Since there islittle literature that addresses the local government website in Selangor and its relationship tothe concept of e-democracy, it is critical to demonstrate the role of e-government in promotinge-democracy. Selangor local government websites can promote e-democracy by exploring threecategories: free and equal access, e-participation, and e-governance. The results show that allfour local government websites perform differently based on the proposed categories and thesurvey conducted. They make different progress and have taken many initiatives to promote edemocracyon their websites. This paper examines the contents of the websites of the selectedlocal governments in Selangor and how they relate to e-democracy. The result shows that thewebsites of different states perform differently. The results collected discuss challenges to theeffectiveness and efficiency of e-government and e-democracy at the local government levelbased on the results collected and interviews conducted with the website administrators.